High prevalence of subclass-specific binding and neutralizing antibodies against Clostridium difficile toxins in adult cystic fibrosis sera: possible mode of immunoprotection against symptomatic C. difficile infection - Monaghan, Tanya M.; Negm, Ola H.; MacKenzie, B.; Hamed, Mohamed R.; Shone, Clifford C.; Humphreys, D.P.; Acharya, K. Ravi; Wilcox, Mark H. (Dove Medical Press, 2017)
Objectives: Despite multiple risk factors and a high rate of colonization for Clostridium difficile, the occurrence of C. difficile infection in patients with cystic fibrosis is rare. The aim of this study was to compare the prevalence of binding C. difficile toxin-specific immunoglobulin (Ig)A, IgG and anti-toxin neutralizing antibodies in the sera of adults with cystic fibrosis, symptomatic C. difficile infection (without cystic fibrosis) and healthy controls.